Strategist : business policy and strategistmanagement - Salavitabar, Hadi (Richard D. Irwin, Inc., 1994)
A strategic planning aid designed to provide a set of structuredoptions which will assist the user in assessing a firm's condition andstrategic position in a variety of situations.